Pengaruh Strategi Pembelajaran Reading, Questioning, And Aswering (RQA)-Terhadap Hasil Belajar Siswa Pada Pokok Bahasan Sistem Persamaan Linear Di Kelas X SMK Negeri 1 Angkola Timur - Muhammad Fahmi Lubis; Susi Sulastri Lubis; Haritsah Hammamah Harahap (Program Studi Matematika Universitas Graha Nusantara Padangsidimpuan, 2023)
This research was conducted at SMK Negeri 1 East Angkola with the aim of 1) To find the average student learning outcomes using RQE learning on the subject of systems of linear equations in two variables at SMK Negeri 1 East Angkola 2) To find out the average results of those who did not use RQE learning strategy on the subject of systems of linear equations in East Angkola 3) To find out whether there is an influence of the RQE learning strategy on mathematics learning outcomes in class X at SMK Negeri 1 East Angkola. This research uses the Quasi Experiment method. Data collection was carried out using the final test technique (post test). The samples in this study were class X RPL 1 and class X RPL 2 where class RPL 1 was used as the experimental class and class RPL 2 was used as the control class. This research data was analyzed using SPSS Anova statistical analysis. The research results show that t count > t table, or Ho is rejected (8.646 > 2.034). So, it can be concluded that there is an influence of the use of the Reading Questioning and Answering learning strategy on the learning outcomes in mathematics for class